Further Purification of the Antihaemophilic Factor (AHF) - Veder, H. A (Thrombosis and Haemostasis, 1966)
A description is given of the further purification of AHF by displacement chromatography on such materials as DEAE-Floc and DEAE-Sephadex. The use of a high ion-exchange capacity, which permits the use of relatively high salt concentrations, together with submaximal loading of the columns produced a high degree of purity of the AHF-preparations. The criteria of purity applied, and some properties of the AHF are described.